Critical sets for families of latin squares - Donovan, Diane (Utilitas Mathematica, 1998)
In this paper I give details of new constructions for critical sets in latin squares. These latin squares, of order n, are such that they can be partitioned into four subsquares each of which is based on the addition table of the integers modulo n/2, an isotopism of this or a conjugate.